2013
DOI: 10.1111/ggi.12052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with rheumatic diseases and chronic joint symptoms in the elderly

Abstract: There was a significant association of rheumatism and symptoms with women and high incomes. Obesity was associated with joint symptoms, which in turn were associated with an impaired quality of life. Cataracts and cardiovascular disease were associated with rheumatism. The identification of these characteristics in the elderly will contribute to a better understanding of this systemic disease and should be used to plan effective preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
1
14
0
3
Order By: Relevance
“…Rheumatic diseases are considered a common cause of disability and represent high costs to public health in Brazil and the United States . Nonsteroidal anti‐inflammatory drugs are used in the treatment of arthritis, but in recent years biological and conventional disease‐modifying anti‐rheumatic drugs (DMARDs) became a new option for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rheumatic diseases are considered a common cause of disability and represent high costs to public health in Brazil and the United States . Nonsteroidal anti‐inflammatory drugs are used in the treatment of arthritis, but in recent years biological and conventional disease‐modifying anti‐rheumatic drugs (DMARDs) became a new option for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatic diseases are considered a common cause of disability and represent high costs to public health in Brazil and the United States. 38,39 Nonsteroidal anti-inflammatory drugs are used in the F I G U R E 5 Treatment with CXCL9(74-103) at late time points has no effect on cell recruitment to the joint in antigen-induced arthritis. Mice were immunized with mBSA and CFA and were challenged i.a.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these relationships have been studied independently in some conditions. For example, diabetes is related to cataracts and diabetic retinopathy, and arthritis has been associated with a higher risk of cataracts [20, 53, 54]. However, it is known that not only diabetes but also hypertension and hypercholesterolemia are risk factors for diabetic retinopathy so, in this case, cumulative effects are possible [55, 56].…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those observed in other studies. 7,9,10 Aging promotes a physiological wear of the joints that, combined with insufficiency in the repair of articular cartilage, mainly in the presence of comorbidities, 25,26 can render the prevalence higher in older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, prevalence rates were respectively 44.2% among elderly individuals from Minas Gerais 8 and 45.6% in an elderly population from São Paulo. 9 With adult populations, to date, the only study found was conducted by Silva et al, 10 who identified a prevalence of 36.5% in the south of Brazil.…”
Section: Introductionmentioning
confidence: 99%